Effects of Hydration Level and Heat Stress on Thermoregulatory Responses, Hematological and Blood Rheological Properties in Growing Pigs - Waltz, Xavier (Public Library of Science, 2014)
Heat stress is one of the major limiting factors of production efficiency in the swine industry. The aims of the present study were 1) to observe if hemorheological and hematological parameters could be associated to physiological acclimation during the first days of heat stress exposure and 2) to determine if water restriction could modulate the effect of thermal heat stress on physiological, hematological and hemorheological parameters. Twelve Large White male pigs were divided into an ad libitum and a water restricted group. All pigs were submitted to one week at 24°C (D-7 to D-1). Then, at D0, temperature was progressively increased until 32°C and maintained during one week (D1 to D7). We performed daily measurements of water and feed intake. Physiological (i.e., skin temperature, rectal temperature, respiratory rate), hematological and hemorheological parameters were measured on D-6, D-5, D0, D1, D2 and D7. Water restriction had no effect on physiological, hematological and hemorheological parameters. The first days of heat stress caused an increase in the three physiological parameters followed by a reduction of these parameters suggesting a successful acclimation of pigs to heat stress. We showed an increase in hematocrit, red blood cell aggregation and red blood cell aggregation strength during heat stress. Further, we observed an important release of reticulocytes, an increase of red blood cell deformability and a reduction of feed intake and blood viscosity under heat stress. This study suggests that physiological acute adaptation to heat stress is accompanied by large hematological and hemorheological changes.